The Kind Millionaire, Lemonade Joe and Superman. On Czech Film Parodies - Mareš, Petr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article deals with Czech film parodies that were produced primarily during the period of the state-directed cinema (1945–1989). Their development was connected to a campaign against trash literature, which attempted in the 1930s and 1940s to suppress different popular genres that were considered worthless and harmful. Parodies caricatured conventions of disapproved genres (romance, western, detective story), but at the same time, maintained an awareness of them and eventually also functioned as a substitute for them. The construction of parodies was often based on the accumulation of motifs of a given genre and their escalation to absurdity. The technique of confrontation of disparate elements was also repeatedly used: the conventionality and artificiality of the world of the parodied genre was unveiled as an encounter with the world, which was presented as real and ordinary.